2017
DOI: 10.21474/ijar01/2950
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol as an Alternative to Regular Blood Transfusion- A New Fetal Haemoglobin Inducer From Natural World.

Abstract: Recent molecular studies of fetal hemoglobin (HbF) regulation have shown promise for the development of clinical HbF inducers to be used in patients with β-thalassemia and sickle cell disease. However, while numerous promising inducers of HbF, have been studied at past in βthalassemia patient with limited success resulted no universally effective agents. Increased production of fetal hemoglobin (HbF) can ameliorate the severity of both β-thalassemia and sickle cell disease (SCD), the major disorders of β-hemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…More recently it was reported that ORF1ab, ORF10, and ORF3a proteins of SARS-CoV-2 have the ability to attack hemoglobin's heme (Wenzhong et al, 2020), causing destruction of porphyrin and inability of erythrocytes to capture and distribute oxygen effectively (Chowdhury et al, 2017). As reported in experimental animal models and clinical studies in thalassemia patients, Resveratrol enhances the expression of γ-globin genes and could be a potent antioxidant and HbF stimulator, leading to improvement of oxygen-binding capacity of hemoglobin.…”
Section: Resveratrol Stimulates Hbf Productionmentioning
confidence: 99%
“…More recently it was reported that ORF1ab, ORF10, and ORF3a proteins of SARS-CoV-2 have the ability to attack hemoglobin's heme (Wenzhong et al, 2020), causing destruction of porphyrin and inability of erythrocytes to capture and distribute oxygen effectively (Chowdhury et al, 2017). As reported in experimental animal models and clinical studies in thalassemia patients, Resveratrol enhances the expression of γ-globin genes and could be a potent antioxidant and HbF stimulator, leading to improvement of oxygen-binding capacity of hemoglobin.…”
Section: Resveratrol Stimulates Hbf Productionmentioning
confidence: 99%